2022
DOI: 10.35912/ijfam.v4i2.905
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Age, Gender, And Ethnic Diversity On Organizational Performance: An Empirical Study Of Bangladesh's Banking Sector

Abstract: Purpose: This study aims to investigate the impact of workforce diversity (in terms of employee age, gender, and ethnicity) on organizational performance in Bangladesh's banking sector. Research Methodology: This research work evaluates the relationship between workforce diversity and organizational performance in the banking sector. The impact of workforce diversity on organizational performance is examined using structural equation modeling (SEM). The sample data was acquired from ten randomly chosen banks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…After validating the measurement model, it was necessary to examine the structural model to validate the proposed hypotheses [ 131 , 136 ]. The structural model was evaluated utilizing path coefficients (β) and R 2 .…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…After validating the measurement model, it was necessary to examine the structural model to validate the proposed hypotheses [ 131 , 136 ]. The structural model was evaluated utilizing path coefficients (β) and R 2 .…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…According to numerous previous studies, SQ criteria are essential for better performance for any digital learning platform. SQ raises the participant's interest and satisfaction with the e-learning portal (Hadoussa, 2020;Shahzad et al, 2021) and increases the intention to system use (Çelik & Ayaz, 2022;Fernando, 2020;Roy, 2022;Shahzad et al, 2021;Shams et al, 2022;Yakubu & Dasuki, 2018) for the e-learning portal. Therefore, the researcher proposes: H5: The impact of SQ on the US differs significantly for students studying business and engineering.…”
Section: System Quality (Sq)mentioning
confidence: 99%
“…To assess the measurement model, researchers check the factor loadings (λ), Cronbach's alpha (α), composite reliability (CR), average variance extracted (AVE), and discriminant validity (Hair et al, 2010;Roy, 2022). From the result, it was found that (see Tab.…”
Section: Measurement Model Assessmentmentioning
confidence: 99%